Composition and nutritive value of ramie leaf flour for monogastric animals - Duarte, Ângela de Almeida; Sgarbieri, Valdemiro Carlos; Júnior, Romeu Benatti (Pesquisa Agropecuaria Brasileira, 1997)
The objective of this research was to study the composition and the nutritive value of ramie (Boehmeria nivea, Gaud) leaf flour. The rat (Ratus norvegicus) was used as experimental model. Chemical determinations showed that ramie leaf flour contained all macronutrients and minerals in excess to the need of growing rats but deficiency of methionine, phosphorus and copper. Complementation of the flour with the three limiting nutrients and vitamins, given to the rats, did not promote growth and caused body weight loss. Pair-fed tests with ramie leaf flour and a reference diet revealed that the rats lost weight and died, due to rejection of the ramie flour and the physiological stress caused by the high content of fiber and phenolic compounds. Autoclaving the ramie flour did not improve the condition and performance of the rats, compared with the unheated flour. Replacement of up to 20% of the reference diet by the complemented ramie flour did not affect the rat growth and performance. Replacements above 25% decreased growth significantly (p≤0.01) and at 40% substitution occurred death of the rats. Treating the diet with 40% substitution by ramie flour with gamma rays (1 Mrad) improved nutritional indexes significantly and eliminated the deaths of the rats.